Костюм театру Кабукі: історія розвитку, типологія, символіка - Рибалко, С. (Інститут народознавства НАН України, 2008)
The costumes in Kabuki plays have no less meaning than actors’ mastery. Actors there had been considered as arbiters in fashion matters. The “Sodo” school (that of putting kimono on) has its source at actors’ practice to change the clothing in the presence of audience.